Pandangan Filsafat Pendidikan Islam Terhadap Kurikulum - Bainar Bainar (LPPM STAI Diniyah Pekanbaru, 2019)
Philosophy is' deep, systematic, radical and universal thinking in the context of the search for truth, essence or nature, about everything in the context of educational philosophy that is more urgent in considering efforts and reflecting reality in the world of education, so that the whole reflections can find truths and policies that are useful for efforts to promote the world of education itself. The object of contemplation about something here is related to Islamic education that is the object of thought, the curriculum that is a set of plans and regulations, concerning the objectives, content and learning materials, as well as the methods used as guidelines, in learning activities to help children achieve educational goals in shaping their personality to guide Islamic teachings based on beliefs and descent from the Koran and Hadith to achieve happiness in the World and the Hereafter. In this case, it includes both the curriculum as a plan and the curriculum as implementation, so that it can keep track of time.